Anti-Inflammatory Effect of Gamisoyo-San in an Animal Model of Amyotrophic Lateral Sclerosis. (21st June 2018) - Park, Sunjung; Yang, Eun Jin
Abstract : Inflammation is considered a critical factor in the pathogenesis of amyotrophic lateral sclerosis (ALS). We aimed to evaluate the effect of the herbal formula Gamisoyo-San (GSS) on the muscles of h S O D 1 G 9 3 A transgenic mice, a mouse model of ALS, by examining the tissue expression of inflammation- and oxidative stress-related proteins. The mice were randomly divided into three groups: nontransgenic mice (non-Tg, n = 4), h S O D 1 G 9 3 A transgenic mice (Tg, n = 4), and GSS-treated h S O D 1 G 9 3 A transgenic mice (Tg+GSS, n = 4). Eight-week-old female h S O D 1 G 9 3 A transgenic mice were fed GSS (1 mg/g body weight) for 6 weeks. Gastrocnemius (GA) tissues were analyzed for inflammatory proteins [CD11b and toll-like receptor 4 (TLR4)] and oxidative stress-related proteins [heme oxygenase 1 (HO1) and ferritin] by western blot analysis. Administration of GSS significantly reduced the level of inflammation- and oxidative stress-related proteins in h S O D 1 G 9 3 A transgenic mice. GSS ameliorated inflammation by downregulating TLR4 and CD11b expression and regulated iron homeostasis in the GA muscle of h S O D 1 G 9 3 A mice. GSS could help reduce inflammation by regulating immune reactions in patients with ALS. To the best of our knowledge, this is the first study to demonstrate the effect of GSS on muscle inflammation in an ALS animal model.